Analisis Peran Lembaga Badan Pemeriksa Keuangan dalam Kemakmuran Masyarakat - Putri Amanda; Putri Indriyanti; Muhammad Arif (Journal of Research and Development on Public Policy, 2023)
This research aims to analyze the role of the BPK in providing financial reports and providing evaluations of state agencies' efforts to optimize community prosperity. Through the use of qualitative systems and strategies for reviewing legislation and literature. The research results show that performance audits are the thing that has the strongest relationship between audits and community prosperity. Performance evaluation is the only test that can guarantee the management of public funds (people's prosperity).